2018
DOI: 10.3390/ijms19030690
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Thiazolyl Resorcinols, Potent and Selective Inhibitors of Human Tyrosinase

Abstract: Tyrosinase inhibitors are of great clinical interest as agents for the treatment of hyperpigmentary disorders; however, most compounds described in the literature lack clinical efficiency due to insufficient inhibitory activity against human tyrosinase (hTyr). Recently, we reported that thiazolyl resorcinols (4-resorcinylthiazol-2-amines and -amides) are both selective and efficacious inhibitors of hTyr in vitro and in vivo. Here, we measured dose-activity profiles of a large number of thiazolyl resorcinols an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 37 publications
1
56
0
3
Order By: Relevance
“…However, the clinical efficacy of current tyrosinase inhibitors is limited due to the fact that they were typically selected based on their ability to inhibit mushroom tyrosinase (Chang, 2009;Lee et al, 2016). In recent studies, Thiamidol was characterized as an especially potent inhibitor of human tyrosinase (Mann et al, 2018a(Mann et al, , 2018b. In vitro, Thiamidol was superior to frequently used inhibitors of hyperpigmentation such as arbutin, kojic acid, and hydroquinone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical efficacy of current tyrosinase inhibitors is limited due to the fact that they were typically selected based on their ability to inhibit mushroom tyrosinase (Chang, 2009;Lee et al, 2016). In recent studies, Thiamidol was characterized as an especially potent inhibitor of human tyrosinase (Mann et al, 2018a(Mann et al, , 2018b. In vitro, Thiamidol was superior to frequently used inhibitors of hyperpigmentation such as arbutin, kojic acid, and hydroquinone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is evident that an effective and safe topical inhibitor of human skin hyperpigmentation is lacking. Recently, more than 50,000 compounds were screened for their ability to inhibit a recombinant human tyrosinase (Cordes et al, 2013) and Thiamidol (isobutylamido-thiazolyl-resorcinol) was identified as an especially potent inhibitor of human tyrosinase (Mann et al, 2018a(Mann et al, , 2018b. In vitro, Thiamidol was superior to frequently used inhibitors of hyperpigmentation, such as arbutin, kojic acid, and hydroquinone.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several azole derivatives (Figure 13) have been studied for their tyrosinase inhibitory activity 388 . The discovered new types of inhibitors included DL-3(5-benzazolyl) alanines and alpha-methyldopa analogs 389 , aryl pyrazoles 390 , heterocyclic hybrids based on pyrazole and thiazolidinone scaffolds 391 , 3,5-diaryl-4,5-dihydro-1H 392 and 3,5-diaryl pyrazole derivatives 393 , pyrazolo[4,3-e][1,2,4]triazine sulfonamides and sildenafil 394–396 , 1,3-oxazine-tetrazole 397 , indole-spliced thiadiazole 398 , benzimidazole-1,2,3-triazole hybrids 399 , 1,2,3-triazole-linked coumarinopyrazole conjugates 400 , isoxazolone derivatives 401 5(4H)-oxazolone derivative 402 , imidazolium ionic liquids 403 , thiazolyl resorcinols 404 have demonstrated the inhibitory effect on tyrosinase. Furthermore, some thiazolidine derivatives have been evaluated for their tyrosinase inhibitory activity including azo-hydrazone tautomeric dyes substituted by thiazolidinone moiety 405 , (Z)-5-(2,4-dihydroxybenzylidene) thiazolidine-2,4-dione 406 , 5-(substituted benzylidene) thiazolidine-2,4-dione derivatives 407 , (2RS,4R)-2-(2,4-dihydroxyphenyl)thiazolidine-4-carboxylic acid 408 , 2-(substituted phenyl) thiazolidine-4-carboxylic acid derivatives 409 and (Z)-5-(3-hydroxy-4-methoxybenzylidene)-2-iminothiazolidin-4-one 410 .…”
Section: Inhibitors From Natural Semisynthetic and Synthetic Sourcesmentioning
confidence: 99%
“…So far, most tyrosinase inhibitors lack clinical efficacy [13] because they were identified by testing on mushroom and not on human tyrosinase [8,14,15]. The purification of soluble variants of human tyrosinase [16] allowed the identification of Thiamidol (isobutylamido thiazolyl resorcinol) as its most potent inhibitor [11,17,18] out of 50 000 screened compounds.…”
Section: Introductionmentioning
confidence: 99%